Different surgical approaches to Scimitar syndrome - Onur Işık; Muhammet Akyüz; Meltem Çakmak; Tülay Demircan; Ali Rahmi Bakiler (KARE Publishing, 2020)
Scimitar syndrome is a rare congenital heart defect characterized by the combination of vascular, bronchial, and parenchymal malformations. This syndrome includes anomalous right pulmonary venous drainage to the inferior caval vein, hypoplastic right pulmonary artery, right lung hypoplasia and the presence of aortopulmonary collaterals to the right lung. In this study, we evaluate the different surgical approaches of 3 cases with Scimitar syndrome who was corrected successfully.